Pathogenicity and pathobiology of Epizootic Ulcerative Syndrome (EUS) causing fungus Aphanomyces invadans and its immunological response in fish - Kumar, Praveen; Sarkar, Purabi; Raju, Stefi V.; V, Manikandan; Guru, Ajay; Arshad, Aziz; Elumalai, Preetham; Arockiaraj, Jesu (Taylor & Francis, 2020)
Aphanomyces invadans, an oomycyte fungus most frequently recognized as a causative agent of epizootic ulcerative syndrome (EUS) is a seasonal epidemic pathogen of great importance in wild and farmed fish in both freshwater and estuarine environments. EUS is a complex infectious etiology which leads to necrosis ulcerative lesions and granulomatous response in fishes. It is a cause of death of approximately 92 species that has been recorded in wild as well as in commercial culture systems worldwide. Several environmental and biological factors are responsible for the growth and establishment of A. invadans, which further attracts secondary pathogens to enter the lesions thus, increasing the severity of the infection. Methods for the proper identification of A. invadans, includes PCR detection and microscopy. However, the pathogenicity of the A. invadans is still unknown. In order to discover new effective treatment to fight the disease, a better understanding of the infection process is necessary. The studies on fungal infection in fishes indicate the immune response pattern in fish against A. invadans that serves as an important key for the development of targeted therapeutics and vaccines to prevent the disease and to maintain EUS free aquaculture systems. The immune mechanisms that respond to stimulation, interaction between the immune system of host species and A. invadans, different factors of A. invadans and its pathogenicity as well as various approaches of treatment has been discussed in this review.